Constructing the Body of Knowledge of Pesantren Education: A Philosophical, Historical, and Curricular Inquiry - Budiman, Agus; Anwar, Saiful; Zarkasyi, Azmi; Lateh, Afifi (At-Ta'dib, 2025)
Purpose - Pesantren education, as Indonesia’s oldest Islamic educational institution, holds a rich tradition of nurturing intellectually and spiritually grounded individuals. However, despite its significant historical and cultural role, pesantren education has lacked a formalized Body of Knowledge (BoK) that could support its academic development within higher education. This study aims to construct and map the BoK of pesantren education to provide a structured epistemological foundation for pesantren-based academic programs. Methods - This research adopts a qualitative library research methodology with analytical and interpretive approaches. Data were collected from classical Islamic texts and contemporary studies on pesantren and Islamic education, and were analyzed using inductive-comparative techniques grounded in Islamic epistemology and educational theory. Findings – The findings indicate that pesantren education is underpinned by an integrative epistemology that combines revelation (naqli), reason (‘aqli), and spiritual insight (‘irfani), and operates through a holistic and adaptive curriculum. The study identifies six key domains forming the BoK: Philosophy of Pesantren Education, Curriculum and Methodology, Leadership and Management, Socio-Anthropology, Innovation, and Classical Islamic Text Studies. Research implications / limitations - This study’s main limitation lies in its conceptual nature, suggesting a need for empirical validation. Its originality lies in the systematic formulation of a pesantren education BoK an academic framework that had not been explicitly mapped before thus offering significant value for curriculum design and academic development in Islamic higher education.